Inhibitory control and drug abuse prevention from research to translation - Bardo, Michael T.; Fishbein, Diana H. 1954-.; Milich, Richard; SpringerLink (Online service). (New York Springer, 2011)
Inhibitory Control and Drug Abuse Prevention From Research to Translation Michael T. Bardo, Diana H. Fishbein, Richard Milich, editors Some of the most promising findings about drug abuse come from research into behavioral inhibitory control processes?specifically, that individuals with substance use disorders have inhibitory control deficiencies compared to non-abusers, and that the impulsivity associated with adolescence may account for young people?s vulnerability toward drug-taking behavior. But while this neurobiological approach has steadily influenced the treatment of addiction, it has had only minor effect on prevention efforts. Inhibitory Control and Drug Abuse Prevention was compiled to help correct this situation, synthesizing what we know about the neuromechanics of risk-taking, and mining its ample potential in addiction prevention. Noted experts review up-to-date neurobehavioral studies regarding inhibitory control in humans and laboratory animals, discuss their implications for age groups at risk for impulse control deficits or dysfunction, and apply these findings to the development of innovative, effective prevention strategies. Among the topics covered in this multidisciplinary volume: ? Genetic and environmental determinants of risk-taking behavior. ? Impaired inhibitory control as a mechanism in drug abuse. ? Childhood inhibitory control deficits and risk for substance use. ? Social influence in inhibitory control. ? Translating research into advocacy and policy. ? Targeting anti-drug public service messages to sensation-seeking youth. Inhibitory Control and Drug Abuse Prevention represents a sea change in understanding addictive behavior, and is timely reading for researchers and practitioners in the fields of drug abuse (as well as related high-risk behaviors, e.g., delinquency, unsafe sex, gambling), health psychology, and neuropsychology.
Translating Research on Inhibitory Control for the Prevention of Drug Abuse -- Animal Models of Behavioral Processes that Underlie the Occurrence of Impulsive Behaviors in Humans -- Monoaminergic Regulation of Cognitive Control in Laboratory Animals -- Genetic and Environmental Determinants of Addiction Risk Related to Impulsivity and Its Neurobiological Substrates -- Impaired Inhibitory Control as a Mechanism of Drug Abuse -- Neuroimaging, Adolescence, and Risky Behavior -- Inhibitory Control Deficits in Childhood: Definition, Measurement, and Clinical Risk for Substance Use Disorders -- Impulsivity and Deviance -- Impulsivity and Adolescent Substance Use: From Self-Report Measures to Neuroimaging and Beyond -- A Functional Analytic Framework for Understanding Adolescent Risk-Taking Behavior -- Peer Influences on Adolescent Risk Behavior -- The Effects of Early Adversity on the Development of Inhibitory Control: Implications for the Design of Preventive Interventions and the Potential Recovery of Function -- Early Risk for Problem Behavior and Substance Use: Targeted Interventions for the Promotion of Inhibitory Control -- Designing Media and Classroom Interventions Targeting High Sensation Seeking or Impulsive Adolescents to Prevent Drug Abuse and Risky Sexual Behavior -- Self-Regulation and Adolescent Drug Use: Translating Developmental Science and Neuroscience into Prevention Practice -- Implications for Translational Prevention Research: Science, Policy, and Advocacy -- Future Directions for Research on Inhibitory Control and Drug Abuse Prevention.
Electronic reproduction.
Keywords: Drug abuse -- Prevention; Drug abuse -- Psychological aspects; Electronic books; Electronic books